PERBEDAAN TINGKAT PROFESIONALISME KERJA AUDITOR DILIHAT DARI JENIS KELAMIN, JABATAN, DAN JENIS AFILIASI KANTOR AKUNTAN PUBLIK - Rifqi Novriyandana (Universitas Trunojoyo Madura, 2015)
Profesionalism is one of the important thing in audit of public accountant. Public accountants have role and ethics when doing their job. Purpose of this research is to get the empirical evidence about difference of auditor profesionalism, if seen from sex, type of affiliation public accountant firm, and position of accountant in public accountant firm by using profesionalism instrument develop by Hall (1968) and Snizek (1972) combine with Meyer and Allen (1984). The sample of this research is auditor at java island, sample was taken by clustered sampling method. Collecting data with direct observation to the public accountants firm in java island by using questioner. Gathered sample counted 136 with 100% respons rate, so all of questioner is back. Examination of hyphothesis use t-test.The result of this research, if seen profesionalism auditor from sex is not found the difference of profesionalism, it means between man and women have same the level of profesionalism. Based on position level at public accountant firm there is difference, it means there is difference level of profesionalism auditor seen by hierarchy. Based on type of affiiation accountans in public accountant firm there is not difference, it means accountants who work at accountant public local and accountant public foreign affiliation are the same level of profesionalism.